Interethnic Trust Issues in a Multicultural Society - Alyona V. Alborova; Svetlana V. Dreeva; Victoria A. Starchenko (СибСкрипт, 2023)
The article describes the problem of trust in interethnic relations. The phenomenon of trust is one of the most important aspects of interethnic interaction in the modern multicultural environment. The trust of ethnophors to ethnocontact groups usually depend on the attitude of trust / distrust towards the world, other people, and oneself, as well as on the type of ethnic identity and personal characteristics. The study involved 280 young people from the North-Caucasian regions of Russia: 80 Ossetians, 80 Chechens, 40 Kabardians, 40 Russians, and 40 Georgians. The data collection relied on the Saks-Levy method of Incomplete Sentences, which was modified by the authors, the Assessment of Trust / Distrust to the World, Others, and Oneself developed by A. B. Kupreychenko, and R. B. Kettell’s 16-Factor Personality Questionnaire. The authors designed their own scale to measure the level of trust in ethno-contact groups. Other research tools included the method developed by N. M. Lebedeva and A. N. Tatarko that assesses the valence and definiteness of ethnic identity, the degree of civic identity, and interethnic attitudes. The respondents, regardless of nationality, believed that trusting interethnic relations are based on accepting foreign national values, customs, and culture, as well as on the certainty that a representative of a different ethnicity will provide help and support in a difficult situation. Those with a low level of interethnic trust demonstrated a much lower all-Russian identity and a much greater anxiety connected with interethnic interaction, compared with the respondents who had a high level of interethnic trust. The latter also had a positive attitude towards other ethnic groups and were ready to interact with other nationalities in various social situations. The respondents with low trust levels were less emotionally stable, more restrained, suspicious, anxious, conservative, and tense.